2007
DOI: 10.1249/01.mss.0000235884.71487.21
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Oxygen Uptake during Fast Running Using Accelerometry and Heart Rate

Abstract: Uni- and triaxial accelerometer outputs have a linear relationship with speed during walking. During running, uniaxial accelerometer outputs plateau because of the biomechanics of running, whereas triaxial accelerometer output has a linear relationship. The combined methodologies predict .VO2 better than either predictor alone; a subject's individually calibrated data further improves .VO2 estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
81
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 28 publications
8
81
3
1
Order By: Relevance
“…While our results were consistent with the linear increase during walking speeds, we did not observe an improved plateau response in the GT1M monitors. The study by Fudge et al (8) did not include the study of sedentary and light physical activity, so differences in the lowest activity count regions could not be analyzed and remain an important area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our results were consistent with the linear increase during walking speeds, we did not observe an improved plateau response in the GT1M monitors. The study by Fudge et al (8) did not include the study of sedentary and light physical activity, so differences in the lowest activity count regions could not be analyzed and remain an important area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, no researchers to date have performed sensor characterization on newer models of the ActiGraph, such as the 71256 (marketed 1999 -2005) and the GT1M (marketed 2005-present), although differences between these device generations have been reported in a human study (8), and these differences have been suggested as a potential source of monitor variability that should be explored in a mechanical setting (5). Cross-generational analyses could provide insight into variations in the device hardware across monitor generations, which could impact the predictions of physical activity intensity or energy expenditure (EE) using devices other than the 7164 monitors.…”
mentioning
confidence: 99%
“…VO 2 ) by the 3DNX model version 2 during treadmill exercise. 15,16 The capability of 3DNX to predict energy expenditure in free-living adult and adolescent cohorts has also been examined using the doubly labelled water method as a criterion measure. Carter et al 17 reported that 35% of the variance in total energy expenditure was explained by the 3DNX output; this increased to 78% when combined with anthropometric variables.…”
Section: Introductionmentioning
confidence: 99%
“…All of them by Cobos include a recording of heart rates by telemetry, a valid system of measurement [15][16][17]. It gives us information about heart response when performing exercises that express a huge variability of intensity [18] and, at the same time, it gives us an energetice information about the performed exercise [19].…”
mentioning
confidence: 99%